Extensive netting in Albasini and Nandoni dams: a potential threat to fish as a sustainable food source in the Vhembe District, South Africa. Issue 2 (27th May 2016) - Barnhoorn, IEJ; van Dyk, JC; Wagenaar, GM
Abstract : Fish populations in Albasini and Nandoni dams are negatively affected by extensive netting practices. This observation was made by the authors following a number of fish health assessment surveys related to aquatic pollution in the Luvuvhu River catchment. A comparison between the number and size of fish collected over a period of ten years indicated decreases in the average size and a consistent low number of fish, despite similar extensive sampling efforts. Unregulated netting is a common practice in both dams. This may become a serious problem as fish from these two dams are an important source of protein for the local communities. The purpose of this note is to report that gillnets are illegally used in the system and on the effect this could have on the fish population. The authors suggest educational and awareness initiatives to inform local communities about the importance of utilising fish in a sustainable manner to ensure the livelihood of generations to come.